Clinical Profile, Pacemaker Parameters and Early Outcome of Permanent Pacemaker Implantation in Lumbini Province Nepal - Gautam, Samir; Dhungel, Sachin; KC, Bishal; Khan, Majhar; Shakya, Abhishesh; Panjiyar, Rajesh; Sharma, Deepanjali (Journal of National Heart and Lung Society Nepal, 2024)
Background: Pacemaker implantation was started for the first time in Lumbini province Nepal at Gautam Buddha Community Heart Hospital. The objective of this research is to evaluate clinical parameters and compare with established centers in Nepal. Methods: Patient and pacemaker parameters noted in proforma after getting consent from the patients. This is simple observational study. Calculation of parameters done using SPSS 17 version.Results: Total 224 patients were evaluated over the duration of 3 years. Majority (60.3%) were female and 39.7% were male. 51.3% were of age group 65 to 80 years. 21% were above age 80 years, 22.8% were 45 to 65 years and 4.9% were below 45 years. 96.4% were Single chamber and 3.6 % were Dual chamber pacemaker. 97.8% were implanted on left side and 2.2% were implanted on right side. Impedance more than 1000 ohm noted in 3.6%. Threshold more than 1 mV noted in 7.6% and R wave amplitude less than 10 noted in 28.1%. Dislodgement was in 2.6% and Infection in 1.3%. No procedural death.Conclusion: Single chamber implantation was far more common than dual chamber. Pacemaker parameters were similar at our hospital to other hospitals in Nepal.